2020
DOI: 10.28991/cej-2020-sp(emce)-05
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Utilisation of Recycled Waste Material as an Alternative Modifier in Asphalt Mixtures

Abstract: The possibility of using waste materials in road construction is of great interest as their utilisation may contribute to reducing the problems of hazard and pollution and conserve natural resources. Thus, there is an urgent need to find a sustainable method for using waste materials as a substitute in the standard asphalt binders. There are several concerns about the physical and chemical properties and mechanical performance of asphalt pavements incorporated with waste material in the effort to reduce perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…The conventional 60/70 penetration grade bitumen provided by Kemaman Bitumen Company Sdn. Bhd Selangor, Malaysia, was used as the base binder with density and flash point equal to 1.02 gm/cm 3 and 240 • C, respectively. The RAP was collected from the PLUS Highway Company Johor, Malaysia, RAP was milled from the North-South Expressway E2 at point 140 km to 148 km.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional 60/70 penetration grade bitumen provided by Kemaman Bitumen Company Sdn. Bhd Selangor, Malaysia, was used as the base binder with density and flash point equal to 1.02 gm/cm 3 and 240 • C, respectively. The RAP was collected from the PLUS Highway Company Johor, Malaysia, RAP was milled from the North-South Expressway E2 at point 140 km to 148 km.…”
Section: Methodsmentioning
confidence: 99%
“…The age of the asphalt mixture is usually between 7-15 years, but numerous asphalt mixtures require major servicing less than 10 years after construction [1,2]. Throughout the service life of the asphalt pavement, bituminous binder suffers from environmental conditions and traffic overload that tend to make an adequate binder viscoelastic, severely oxidized, and increasingly aged [3]. These factors directly influence the behavior of the asphalt pavement.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the application of fiber in asphalt modification is significant and showing an obvious impact of producing a modifier binder with environmentally friendly method. The encouraging of utilizing types of fiber-reinforced in asphalt pavement mixture contains waste fiber, cellulose, glass fibers and synthetic polymer [34,35]. However, the suitable fiber content to be used in a specified mixture may become practically standard for certain fiber types.…”
Section: Waste Fibermentioning
confidence: 99%
“…Several studies have explored the effect of using modifiers on asphalt binder and mixture properties. The results of these studies showed that polymer modification could alter binder properties by increasing the softening point [ 1 , 2 , 3 , 4 , 14 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], increasing the viscosity [ 3 , 37 , 39 , 40 ], decreasing the penetration [ 2 , 3 , 14 , 37 , 38 ], and improving the performance grade [ 2 , 4 , 6 , 37 , 41 ]. For asphalt mixture, the previous studies indicated that polymers could improve the mechanical properties of asphalt mixture, such as resilient modulus [ 14 , 42 , 43 , 44 , 45 , 46 ], fatigue cracking resistance [ 4 , 14 , 47 , 48 , 49 , 50 , 51 ], and rutting resistance [ 43 , 50 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%